1969
DOI: 10.1243/jmes_jour_1969_011_022_02
|View full text |Cite
|
Sign up to set email alerts
|

Control Forces in Rocket Nozzles Produced by a Secondary Gas Stream Inclined at Various Angles to the Nozzle Axis

Abstract: The side force produced by the injection of secondary gas into the supersonic regime of a main nozzle is investigated with particular reference to the effect of the angle between the secondary jet and the main nozzle axis. In the experiments, downstream and upstream injection angles at one secondary port location in the main nozzle were examined. It is shown that there is a definite advantage to be gained by injecting the secondary gas in an upstream direction. An analytical analysis of the results indicates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1970
1970
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 2 publications
2
7
0
Order By: Relevance
“…Other than position of the injection port, the angle of injection and shape of the injection represent geometrical parameters that need to be considered in SITVC optimization process. As previously reported by Nielson et al [19], it is found that secondary injection inclined upstream with respect to the nozzle axis has positive e¨ect on the main §ow de §ection until some experimentally found breakdown value. Injection with upstream inclination angle causes ¤pushes¥ of the edge of a bow shock upstream in §icting stronger adverse pressure gradient and early separation (see Fig.…”
Section: Flow Visualization and Qualitative Analysissupporting
confidence: 75%
See 3 more Smart Citations
“…Other than position of the injection port, the angle of injection and shape of the injection represent geometrical parameters that need to be considered in SITVC optimization process. As previously reported by Nielson et al [19], it is found that secondary injection inclined upstream with respect to the nozzle axis has positive e¨ect on the main §ow de §ection until some experimentally found breakdown value. Injection with upstream inclination angle causes ¤pushes¥ of the edge of a bow shock upstream in §icting stronger adverse pressure gradient and early separation (see Fig.…”
Section: Flow Visualization and Qualitative Analysissupporting
confidence: 75%
“…In the experiments and preliminary numerical simulations, transverse injection is normal to the nozzle axis. As it is reported by Nielson et al [19] and Deere [4], upstream inclined injection has augmenting e¨ects on the side force and vector de §ection angle δ. In order to investigate upstream inclined injection e¨ect, injectors inclined upstream ranging from 20…”
Section: Geometry Of the Secondary Injectionsupporting
confidence: 60%
See 2 more Smart Citations
“…Among different types of FTV as skewing of the throat sonic line or Coanda's effect counter and co flow injection, direct transverse injection into divergent portion of the C-D nozzle is selected as a straightforward and efficient technique for diverting the nozzle jet. Number of mentioned FTV types has been investigated and reported for planar 2D nozzles and some for the axisymmetric nozzles as well, appearing in the works of Wing and Guiliano, 2 Nielson et al, 3 Deere et al, 4 Zmijanovic et al 5 In the mentioned investigations, secondary injection thrust vector control (SITVC) efficiency was confirmed over wide range of pressure ratios which should satisfy needs for the second stage launcher nozzle operation envelope.…”
Section: Introductionmentioning
confidence: 99%